Identification of Natural Lighting Intensity in the Architectural Studio Classroom - Utamisari, Salsabila Febri; Refranisa (Institut Teknologi dan Bisnis Ahmad Dahlan, 2025)
An architectural work has different benefits to support the activities of its users. One of the learning supports for students is space to carry out learning. For architecture students, this architectural studio space is a very necessary space for carrying out learning activities. Natural light is the best source of lighting for every room. The aim of this research is to examine architecture studio rooms as a support for architecture students' learning so that students can study comfortably without using natural lighting. In this research, the method used is to describe data and information from direct observation. This analysis uses quantitative analysis by comparing the conditions in the field with information obtained from the literature. Based on the research, it was found that several areas of the architectural study room received appropriate natural lighting while several other areas received less suitable natural lighting. Therefore, several additional studies are needed in designing lighting. This research aims to provide insights regarding the natural lighting of a building which is calculated using measuring instruments in the field.